Casting a wide net for anemia in advanced prostate cancer: A case series - Zafar, Aneeqa; Veeravelli, Sumana; Iczkowski, Kenneth; Graff, John Paul; Kaesberg, Paul; Parikh, Mamta (Current problems in cancer. Case reports, 2025)
Anemia is a common occurrence in patients with prostate cancer and has numerous associated etiologies including androgen deprivation, radiation toxicity, bone marrow infiltration from cancer, anemia of chronic inflammation, poor nutritional status and bone marrow suppression from chemotherapy. Anemia in metastatic castration resistant prostate cancer (mCRPC) has been associated with a worse prognosis. While anemia associated with solid tumors generally is attributable to either the malignancy or the treatment given for the malignancy, prostate cancer is unique in that it is an indolent disease with fewer cytotoxic treatments and primarily affecting a geriatric population, thus leading to more varied causes of anemia. Non-treatment related causes of anemia ought to be recognized to prevent further morbidity and mortality in this vulnerable patient population. We outline cases that exemplify this spectrum.